Anode materials and batteries
By designing a negative electrode material structure with control pore volume and particle space collapse ratio, the powdering problem of silicon negative electrode material caused by volume expansion in lithium-ion batteries is solved, the circulation performance and first-time Coulomb efficiency are improved, and more stable Electrochemical properties.
Patent Information
- Application Number
- CN202411131888.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-08-19
AI Technical Summary
Silicon negative electrode materials are powdered due to volume expansion in lithium-ion batteries, destroying the electrical contact between active substances and current collectors, reducing electrochemical performance and cycling stability, making it difficult to commercially apply.
A negative electrode material, including a first matrix and a second matrix, has a structure that controls the pore volume and particle space collapse ratio, adjusts the rigid strength of the material by pressurizing treatment, improves structural stability and reduces expansion rate.
It improves the circulation performance of the negative electrode material and the first Coulomb efficiency, extends the service life of the battery, solves the problems of crushing and cracking of the electrode sheet during the pressing roller, and improves the electrochemical performance.
Smart Images

Figure CN118658983B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery materials, and in particular to negative electrode materials and batteries using the negative electrode materials. Background Art
[0002] Lithium-ion batteries are widely used in electric vehicles and consumer electronics due to their high energy density, excellent output power, long cycle life and low environmental pollution. In order to further improve the energy density of batteries, the research and development of silicon negative electrode materials has become particularly important.
[0003] However, silicon negative electrode materials undergo significant volume expansion during the process of lithium insertion and extraction, which causes them to pulverize and fall off the current collector during the charge and discharge process. This will destroy the electrical contact between the active material and the current collector, resulting in a decrease in electrochemical performance, capacity attenuation, and cycle stability, making it difficult to commercialize them. Summary of the invention
[0004] In order to solve at least one of the above technical problems, an embodiment of the present application provides a negative electrode material.
[0005] In addition, an embodiment of the present application also provides a battery comprising the aforementioned negative electrode material.
[0006] The present application provides a negative electrode material, including an active material, wherein the active material includes a first matrix and a second matrix, the negative electrode material has pores, the pore volume of the negative electrode material is M, the pore volume of the negative electrode material measured after being maintained at a pressure of 80 MPa for 1 hour is N, and the particle space collapse ratio of the negative electrode material is P, P=(MN) / M, wherein 0.002 cm 3 / g≤M≤0.12cm 3 / g, 0.05≤P≤0.85.
[0007] In some possible embodiments, the first matrix includes a single substance or a combination of at least one selected from silicon, germanium, antimony, tin and boron.
[0008] In some possible embodiments, the first matrix includes a silicon-based material, and the silicon-based material includes at least one of amorphous silicon, crystalline silicon, a composite of crystalline silicon and amorphous silicon, silicon oxide, and a silicon alloy.
[0009] In some possible embodiments, the second matrix satisfies at least one of the following conditions:
[0010] (1) The second matrix includes a carbon material, and the carbon material includes at least one of artificial graphite, natural graphite, amorphous carbon, activated carbon, mesophase carbon microbeads, carbon nanotubes, carbon nanofibers and graphene;
[0011] (2) The second matrix includes a non-carbon material, and the non-carbon material includes at least one of a metal, a metal oxide, a silicide, a silicate, a phosphate, a titanate, and an aluminum borate.
[0012] In some possible embodiments, at least some of the particles of the second matrix are located inside the particles of the first matrix.
[0013] In some possible embodiments, the negative electrode material further includes a coating layer, which is disposed on at least a portion of the surface of the active material, and the coating layer satisfies at least one of the following conditions:
[0014] (1) The coating layer includes a carbon material, and the carbon material includes at least one of graphene, soft carbon and hard carbon;
[0015] (2) The coating layer includes a metal oxide layer, and the material of the metal oxide layer includes at least one of titanium oxide, aluminum oxide, lithium oxide, cobalt oxide and vanadium oxide;
[0016] (3) The coating layer includes a nitride layer, and the material of the nitride layer includes at least one of titanium nitride, vanadium nitride, cobalt nitride, nickel nitride and carbon nitride;
[0017] (4) The thickness of the coating layer is 0.1 nm to 100 nm.
[0018] In some possible embodiments, the silicon-based material satisfies at least one of the following conditions:
[0019] (1) The average particle size of the primary particles of the silicon-based material is 1 nm to 100 nm;
[0020] (2) The average grain size of the silicon-based material is 0.5 nm to 15 nm.
[0021] In some possible embodiments, the negative electrode material satisfies at least one of the following conditions:
[0022] (1) The median particle size of the negative electrode material is 0.2µm~15µm;
[0023] (2) The specific surface area of the negative electrode material is 0.8 m 2 / g~15m 2 / g;
[0024] (3) The average diameter of the pores is 0.5 nm to 20 nm;
[0025] (4) The compacted density of the negative electrode material powder is 0.8 g / cm 3 ~1.5g / cm 3 .
[0026] In some possible embodiments, the negative electrode material satisfies at least one of the following conditions, calculated by mass percentage:
[0027] (1) The second matrix includes a carbon material, and the content of carbon in the negative electrode material is 5% to 70% based on the mass of the negative electrode material;
[0028] (2) Based on the mass of the negative electrode material, the content of oxygen in the negative electrode material is less than or equal to 10%.
[0029] An embodiment of the present application further provides a battery, which includes a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the negative electrode plate includes the negative electrode material as described above.
[0030] Compared with the prior art, the negative electrode material provided in the embodiment of the present application adjusts the rigidity strength of the negative electrode material by controlling the pore volume M and N before and after the negative electrode material is pressurized. According to the pore volume M of the negative electrode material before pressurization, the pore volume of the negative electrode material after pressurization is N, and the particle space collapse ratio P of the negative electrode material is controlled within a suitable range. By adjusting the rigidity strength of the negative electrode material, on the one hand, the pulverization problem caused by excessive stress generated in the process of lithium insertion and extraction of the negative electrode material is improved, the structural stability of the negative electrode material in the lithiation process is improved, and the cycle performance of the negative electrode material is improved; on the other hand, the internal collapse ability of the negative electrode material is utilized, so that the negative electrode material tends to expand inwardly, thereby reducing the deformation degree of the entire surface of the negative electrode material particles, reducing the expansion rate of the negative electrode material, and thus improving the first coulombic efficiency of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 A process flow chart of the method for preparing the negative electrode material provided in an embodiment of the present application.
[0032] Figure 2 A schematic diagram of the structure of a battery provided in an embodiment of the present application.
[0033] Figure 3 This is a scanning electron microscope image of the negative electrode material of Example 1 of the present application.
[0034] Figure 4 This is the X-ray diffraction pattern of the negative electrode material of Example 1 of the present application.
[0035] Figure 5 This is a cycle performance curve of a battery prepared with the negative electrode material of Example 1 of the present application. DETAILED DESCRIPTION
[0036] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0037] In order to solve the problem of poor conductivity and cycle stability of negative electrode materials, researchers have tried to use coating methods. However, the existing coating preparation process is quite complicated, and the negative electrode material will undergo large volume expansion and contraction during the charge and discharge process, which may cause the coating layer to rupture and fail, and cannot protect the negative electrode material from structural damage, and cannot effectively improve the electrochemical performance of the negative electrode material.
[0038] The inventors of the present application have found that changes in the number and volume of pores in the negative electrode material before and after being compressed will have a significant impact on the volume expansion and performance of the negative electrode material. To this end, the present application embodiment provides a negative electrode material, which includes an active substance, the active substance includes a first matrix and a second matrix, the negative electrode material has pores, the pore volume of the negative electrode material is M (that is, the pore volume of the negative electrode material in a natural state or in an unpressurized state), the pore volume of the negative electrode material measured after being maintained at a pressure of 80 MPa for 1 hour is N, and the particle space collapse ratio P of the negative electrode material is specified as (MN) / M, that is, P=(MN) / M, wherein 0.002cm 3 / g≤M≤0.12cm 3 / g, 0.05≤P≤0.85. By controlling the pore volume M and N of the negative electrode material before and after pressurization, the particle space collapse ratio P of the negative electrode material is adjusted within a suitable range, and the rigidity strength of the negative electrode material is adjusted, so as to improve the electrochemical properties of the negative electrode material while ensuring the structural stability of the negative electrode material, such as improving the cycle stability of the battery prepared by the negative electrode material; solving the problem that the pole piece prepared by the negative electrode material is prone to breakage and cracks during the roller pressing process, and improving the processing performance of the negative electrode material.
[0039] Specifically, under appropriate pressure, controlling the spatial collapse ratio P of the negative electrode material particles in the range of 0.05 to 0.85 can improve the rigidity of the material, moderately reduce the pores inside the negative electrode material, reduce the deformation of the outer surface of the negative electrode material, and ensure that a stable solid electrolyte film is formed on the surface of the negative electrode material, thereby improving the first coulomb efficiency of the negative electrode material. If the spatial collapse ratio of the negative electrode material particles is too low (lower than 0.05), the huge stress generated after the lithiation of the first matrix (such as silicon) will break the entire negative electrode material, resulting in deterioration of the cycle performance of the battery prepared by the negative electrode material; if the spatial collapse ratio of the negative electrode material particles is too high (higher than 0.85), the rigidity of the negative electrode material is weak and there are more internal pores. Although the volume expansion of the first matrix can be effectively alleviated, due to the large volume shrinkage of the negative electrode material, the electrolyte will be absorbed into the material to cause a side reaction between the negative electrode material and the electrolyte, thereby causing serious capacity decay of the battery prepared by the negative electrode material.
[0040] The size of the pore volume M of the negative electrode material directly affects the spatial collapse ratio P of the negative electrode material particles. In order to control the particle spatial collapse ratio P within the range of 0.05~0.85, the negative electrode material needs to have a suitable pore volume M.
[0041] The pore volume M of the negative electrode material needs to be controlled at 0.002 cm 3 / g~0.12cm 3 / g range, this is due to the pore volume M being too large (greater than 0.12cm 3 / g) will lead to the negative electrode material structure being too loose and the pore volume M being too small (less than 0.002cm 3 / g) will cause the negative electrode material particles to be unable to effectively alleviate the volume expansion of active materials such as silicon particles, and will be broken and pulverized. During the cycle of the battery prepared by the negative electrode material, the loose structure of the negative electrode material or the pulverization of the particles will cause a significant change in volume, resulting in capacity decay. The pore volume M is controlled at 0.002cm 3 / g~0.12cm 3 / g, which can effectively extend the service life and cycle stability of the battery prepared with the negative electrode material. Limiting the range of the pore volume M can also adjust the specific surface area and ion diffusion path of the negative electrode material, which is beneficial to improve the electron transfer rate and ion diffusion rate of the negative electrode material, thereby improving the charge and discharge efficiency of the battery prepared with the negative electrode material.
[0042] The pore volume M of the negative electrode material comes from the pores of the negative electrode material. By adjusting the pore size of the pores inside the negative electrode material, the pore volume of the negative electrode material is adjusted and the particle space collapse ratio of the negative electrode material is controlled to meet the requirements of stability and performance of the battery material during use.
[0043] In some embodiments, the average diameter of the pores of the negative electrode material can be 0.5nm~20nm, and can be 0.5nm, 1nm, 2nm, 5nm, 8nm, 10nm, 15nm or 20nm, etc., and of course, it can also be other values within the above range, which are not limited here. The diameter of the pore affects the specific surface area of the negative electrode material. Smaller pores usually have higher specific surface area, which is conducive to the diffusion of electrolytes and ions, while larger pores can improve the expansion performance of the negative electrode material, which helps the stability and cycle life of the negative electrode material. Within the above range, the negative electrode material can reduce the penetration of electrolytes into the negative electrode material while maintaining structural stability and promoting the rapid diffusion of ions, and reduce the side reactions between the negative electrode material and the electrolyte. At the same time, the pore volume and particle space collapse ratio of the negative electrode material are further adjusted, and the average diameter of the pores can be 2nm~15nm.
[0044] In some embodiments, the first matrix may include a single substance or a combination of at least one selected from silicon, germanium, antimony, tin, and boron, etc. For example, silicon particles are used as a component of the negative electrode active material, which can increase the specific capacity of the negative electrode material and thus increase the energy density of the battery prepared from the negative electrode material.
[0045] In some embodiments, the first matrix may include a silicon-based material, and the silicon-based material may include amorphous silicon, crystalline silicon, or a composite of crystalline silicon and amorphous silicon. For example, the first matrix includes amorphous silicon, and amorphous silicon expands isotropically during the lithium insertion process, which can reduce the collapse of pores in the negative electrode material, inhibit the rapid attenuation of the specific capacity of the negative electrode material, and is more conducive to improving the lithium insertion cycle performance of the negative electrode material.
[0046] In some embodiments, the first matrix may include a silicon-based material, and the silicon-based material may include at least one of silicon oxide and silicon alloy.
[0047] In some embodiments, the morphology of the first matrix may include at least one of a dot shape, a sphere shape, an ellipsoid shape, and a plate shape.
[0048] In some embodiments, the purity of the first matrix can be greater than 99%. Taking silicon particles as an active material as an example, high-purity silicon particles are more conducive to Li-Si alloying with lithium, thereby improving the cycle performance of lithium-ion batteries.
[0049] In some embodiments, the second matrix may include a carbon material, and the carbon material may include at least one of artificial graphite, natural graphite, amorphous carbon, activated carbon, mesophase carbon microbeads, carbon nanotubes, carbon nanofibers, and graphene, etc. The second matrix may be selected from the above materials, all of which can play a role in forming a conductive network with the first matrix.
[0050] In some embodiments, the second matrix may include a non-carbon material, and the non-carbon material may include at least one of a metal, a metal oxide, a silicide, a silicate, a phosphate, a titanate, and an aluminum borate. It is understandable that the non-carbon material adopts the above materials, all of which have good strength and rigidity, so that the negative electrode material can have a higher compaction density during the battery preparation process, can improve the structural stability of the negative electrode material, reduce the particle crushing and pulverization of the negative electrode material, and is conducive to improving the cycle performance of the negative electrode material. At the same time, due to its electronic insulation, the non-carbon material usually has good ionic conductivity, which can play a role similar to that of an artificial SEI film, can slow down the subsequent generation of a natural SEI film, reduce the direct contact between the negative electrode material and the electrolyte, and reduce the occurrence of side reactions.
[0051] In some embodiments, the metal oxide may include at least one of aluminum oxide, zirconium oxide, germanium dioxide, and manganese dioxide.
[0052] In some embodiments, the silicide may include at least one of silicon carbide and silicon nitride.
[0053] In some embodiments, the silicate may include at least one of cordierite, mullite and zeolite. It is understood that the silicate of the present application is mainly a natural silicate mineral, wherein cordierite (magnesium aluminum silicate) has a chemical formula of Mg2Al4Si5O 18 , which may contain elements such as Na, K, Ca, Fe and Mn and H2O; mullite, whose chemical formula is 3Al2O3-2SiO2; zeolite (aluminosilicate), whose chemical formula is A m B p O 2p ·nH2O, where A represents cations, usually monovalent or divalent metal ions such as Ca, Na, K, Ba, Sr, etc., B represents the basic units that constitute the zeolite framework structure, namely Si and Al atoms, p is the valence of the cation, m is the number of cations A, and n is the number of water molecules.
[0054] In some embodiments, the phosphate may include at least one of aluminum phosphate, magnesium phosphate, calcium phosphate, titanium phosphate, chromium phosphate, cobalt phosphate, nickel phosphate, germanium phosphate, zirconium phosphate, niobium phosphate, molybdenum phosphate, tantalum phosphate, tungsten phosphate, and lanthanum phosphate.
[0055] In some embodiments, the titanate may include at least one of calcium titanate, iron titanate, lithium titanate, and barium titanate.
[0056] In the negative electrode material, at least part of the particles of the second matrix are located inside the particles of the first matrix. For example, a silicon-based material is selected as the first matrix and a carbon material is selected as the second matrix. The silicon material exists in the form of silicon grains. A plurality of silicon material particles constitute the matrix of the negative electrode material. The silicon material is used as the matrix. The negative electrode material can adjust the various properties of the negative electrode material by utilizing the nanostructure and pore distribution of the silicon material. At least part of the carbon material can be located in the pores of the silicon material and together with the silicon material form the pores of the negative electrode material. In this way, the carbon material is filled into the pores of the silicon material, retaining a certain pore volume to obtain a suitable particle space collapse ratio, thereby adjusting the rigidity strength of the negative electrode material.
[0057] In some embodiments, the average particle size of the primary particles of the silicon-based material can be 1nm~100nm, and can be 1nm, 5nm, 10nm, 15nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or 100nm, etc., and of course, it can also be other values within the above range, which are not limited here. Controlling the average particle size of silicon particles in the silicon-based material between 1nm and 100nm can adjust the specific surface area and electron transfer path of the negative electrode material, which is beneficial to improve the electrochemical performance of the negative electrode material. Further, the average particle size of the primary particles of the silicon-based material can be 5nm~50nm. In the present invention, the expression "primary particle" means the primary structure of a single particle, and the expression "secondary particle" means an aggregate of primary particles aggregated by physical or chemical bonding between primary particles, i.e., a secondary structure, without deliberately performing the aggregation or combination process of the primary particles constituting the secondary particles.
[0058] In some embodiments, the average grain size of the silicon-based material can be 0.5nm~15nm, and can be 0.5nm, 1nm, 2nm, 5nm, 8nm, 10nm, 12nm or 15nm, etc., and of course, it can also be other values within the above range, which are not limited here. Smaller nano-scale silicon grain sizes usually have higher specific surface areas, which are beneficial to charge transfer and ion diffusion of negative electrode materials, and inhibit volume expansion, thereby improving the electrochemical performance, stability and cycle life of negative electrode materials. Further, the average grain size of the silicon-based material can be 2nm~10nm.
[0059] Furthermore, the negative electrode material may also include a coating layer, which is disposed on at least part of the surface of the above-mentioned active material. The coating layer is conducive to improving the structural stability and conductivity of the negative electrode material. The synergistic effect of the appropriate particle space collapse ratio of the negative electrode material and the uniform coating layer on the surface of the negative electrode material can further improve the structural stability of the negative electrode material during the lithiation process, reduce the expansion rate of the negative electrode material, and is conducive to forming a stable solid electrolyte film on the surface of the negative electrode material, and is also conducive to improving the conductivity of the negative electrode material, thereby improving the electrochemical performance of the negative electrode material.
[0060] In some embodiments, the coating layer may include a carbon material, and the carbon material may include at least one of graphene, soft carbon, and hard carbon. Reasonable design of the carbon material raw material of the negative electrode material can effectively inhibit the volume expansion of the negative electrode material and reduce the structural damage of the negative electrode material during the cycle; it can also enhance the mechanical strength and compressive resistance of the negative electrode material.
[0061] In some embodiments, the coating layer may include a metal oxide layer, and the material of the metal oxide layer may include at least one of titanium oxide, aluminum oxide, lithium oxide, cobalt oxide, and vanadium oxide.
[0062] In some embodiments, the coating layer may include a nitride layer, and the material of the nitride layer may include at least one of titanium nitride, vanadium nitride, cobalt nitride, nickel nitride and carbon nitride.
[0063] In some embodiments, the thickness of the coating layer may be 0.1 nm to 100 nm. For example, the thickness of the coating layer may be 0.1 nm, 5 nm, 10 nm, 30 nm, 50 nm, 80 nm, 100 nm, or any value within the range formed by any two of the above values. The coating layer may reduce the solubility of the negative electrode material, thereby reducing the amount of gas produced by the reaction of the dissolved active substance with the electrolyte. Controlling the thickness of the coating layer within the above range is beneficial to maintaining the stability of the particle structure of the negative electrode material during the cycle, and can reduce the exposed active substance on the surface of the negative electrode material. Further, the thickness of the coating layer may be 1 nm to 50 nm, and further, the thickness of the coating layer may be 1 nm to 20 nm, which is beneficial to the rapid and reversible deintercalation of lithium ions.
[0064] In some embodiments, the coating layer may be a single-layer coating layer formed of the above-mentioned single material, or a coating layer formed by a combination of the above-mentioned multiple materials, or a multi-layer coating layer formed of a single material, or a multi-layer coating layer formed of multiple materials, etc. The layer structure of the coating layer can be selected according to actual needs. It can be understood that when the coating layer is a multi-layer coating structure, the density is higher.
[0065] In some embodiments, the median particle size of the negative electrode material can be 0.2µm~15µm, and can be 0.2µm, 0.5µm, 1µm, 2µm, 5µm, 10µm or 15µm, etc., and can also be other values within the above range, which are not limited here. The median particle size of the negative electrode material directly affects the specific surface area and electron transfer path of the negative electrode material. A smaller particle size usually means a larger specific surface area, which is conducive to the electrochemical reaction and the rapid charge transfer, thereby improving the power density and energy density of the battery; a smaller particle size can reduce the volume change of the material during the lithium ion insertion / extraction cycle, which helps to reduce the stress and deformation of the structure, thereby extending the cycle life of the battery; the range of the median particle size can further affect the pore structure and pore volume of the negative electrode material, and affect the particle space collapse ratio of the negative electrode material. Further, the median particle size of the negative electrode material can be 1µm~10µm.
[0066] In some embodiments, the specific surface area of the negative electrode material can be 0.8 m 2 / g~15m 2 / g, which can be 0.8m 2 / g, 1m 2 / g, 2m 2 / g, 5m 2 / g, 8m 2 / g, 10m 2 / g or 15m 2 / g, etc., and of course, other values within the above range can also be used, which are not limited here. Within the above range, it is beneficial to the rapid progress of electrochemical reactions and charge transfer, thereby improving the electrochemical performance of the negative electrode material. Further, the specific surface area of the negative electrode material can be 2m 2 / g~10m 2 / g.
[0067] In some embodiments, the powder compaction density of the negative electrode material can be 0.8 g / cm 3 ~1.5g / cm 3 , which can be 0.8 g / cm 3 , 0.9g / cm 3 , 1g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 or 1.5g / cm 3Of course, it can also be other values within the above range, which is not limited here. Within the above compaction density range, the negative electrode material has a suitable charge transfer rate and electrolyte contact area, and also has suitable good structural stability. Further, the powder compaction density of the negative electrode material can be 1g / cm 3 ~1.2g / cm 3 .
[0068] In some embodiments, the carbon content of the negative electrode material can be 5% to 70% based on the mass of the negative electrode material, and can be 5%, 10%, 20%, 30%, 40%, 50%, 60% or 70% by weight, etc., and can also be other values within the above range, which are not limited here. Within the above range, by adjusting the carbon content, the electrochemical performance and structural stability of the negative electrode material can be optimized. Further, the carbon content of the negative electrode material can be 10% to 60%.
[0069] In some embodiments, the negative electrode material also contains oxygen elements, calculated as a percentage by mass, based on the mass of the negative electrode material, the mass fraction of oxygen elements in the negative electrode material can be less than or equal to 10%, illustratively 1%, 3%, 5%, 8% or 10%, etc., and of course other values within the above range can also be used, which are not limited here. The introduction of a certain amount of oxygen elements can affect the structure and chemical properties of the negative electrode material and adjust the pore structure of the negative electrode material. During the synthesis of the negative electrode material, the oxygen elements within the above content range can form oxides or functional groups with a high oxygen content with carbon and silicon atoms, which can form pores in the negative electrode material or adjust the distribution and size of the pores of the negative electrode material; it can also improve the mechanical properties and structural stability of the negative electrode material; improve the electronic conductivity of the negative electrode material and the kinetic characteristics of the electrochemical reaction, which helps to improve the charge and discharge efficiency of the battery prepared by the negative electrode material; in addition, it may also affect the surface chemical properties of the negative electrode material, such as the formation of surface active sites, further promote the interaction between the negative electrode material and the electrolyte, and optimize the overall performance of the battery.
[0070] Compared with the prior art, the negative electrode material provided in the embodiment of the present application has the following beneficial effects:
[0071] 1. The embodiment of the present application controls the pore volume M and N of the negative electrode material before and after pressurization, controls the particle space collapse ratio P of the negative electrode material within the range of 0.05 to 0.85, and adjusts the rigid strength of the negative electrode material. On the one hand, the pulverization problem caused by excessive stress generated by the first matrix in the negative electrode material during the lithium extraction process is improved, the structural stability of the negative electrode material during the lithiation process is improved, and the cycle performance is improved; on the other hand, the internal collapse ability of the negative electrode material is utilized to guide the negative electrode material to tend to expand inward, so that the entire particle surface deformation is smaller, thereby improving the first efficiency of the battery prepared by the negative electrode material, and effectively reducing the expansion rate of the negative electrode material. Thereby ensuring that the volume expansion effect of the negative electrode material is reduced, the external deformation of the negative electrode material is stabilized, and a stable solid electrolyte membrane is formed, the electrochemical performance of the negative electrode material is improved, such as improving the cycle stability of the battery prepared by the negative electrode material; solving the problem that the pole piece prepared by the negative electrode material is prone to breakage and cracking during the roller pressing process, and solving the problem of poor processing performance of the negative electrode material.
[0072] 2. The negative electrode material provided in the embodiment of the present application deposits a second matrix inside the first matrix and forms pores, thereby adjusting the pore volume of the negative electrode material, controlling the particle space collapse ratio of the negative electrode material, thereby reducing the expansion rate of the negative electrode material, and improving the electrochemical performance of the negative electrode material; in addition, the negative electrode material also has a coating layer. The formation of the coating layer on the surface of the negative electrode material can reduce the dissolution amount of the negative electrode material during the cycle, thereby reducing the side reactions occurring when the dissolved first matrix contacts the electrolyte.
[0073] See also Figure 1 As shown, the method for preparing the negative electrode material provided in the embodiment of the present application specifically comprises the following steps:
[0074] Step S1, sintering the first material once to obtain a first product.
[0075] Specifically, the first material is placed in a reaction device (such as an atmosphere furnace), sintered once under a protective atmosphere, and then cooled to obtain a first product. The main purpose of sintering the first material once is to pretreat the first material, prevent oxidation, and promote the pyrolysis and crystallization process of the first material, so as to stabilize the structure of the first product, prepare for subsequent chemical reactions and compounding steps, and ensure that the first product has a certain crystal structure and chemical activity.
[0076] In some embodiments, the first material may include a single substance or a combination of at least one selected from silicon, germanium, antimony, tin, and boron, etc. For example, silicon is used as the first material to increase the specific capacity of the prepared negative electrode material, thereby increasing the energy density of the battery prepared from the negative electrode material.
[0077] In some embodiments, the first material may include a silicon-based material, and the silicon-based material may include amorphous silicon, crystalline silicon, or a composite of crystalline silicon and amorphous silicon.
[0078] In some embodiments, the first material may include a silicon-based material, and the silicon-based material may include at least one of silicon oxide and silicon alloy.
[0079] In some embodiments, the morphology of the first material may include at least one of a dot shape, a sphere shape, an ellipsoid shape, and a flake shape.
[0080] In some embodiments, the purity of the first material may be greater than 99%. Taking silicon as the first material as an example, high-purity silicon is more conducive to Li-Si alloying with lithium, thereby improving the cycle performance of lithium-ion batteries.
[0081] In some embodiments, the median particle size D50 of the first material can be 0.1μm~20μm, and can be 0.1μm, 5μm, 8μm, 10μm, 12μm, 15μm or 20μm, etc. Within the above-defined range, it helps to ensure the uniformity and consistency of the first material during heat treatment and chemical reaction. At the same time, a smaller particle size helps to improve the specific capacity of the battery and reduce the volume expansion of the negative electrode material. Further, the median particle size D50 of the first material can be 2μm~15μm. The particle size test method of the above-mentioned first material can be tested by Malvern laser particle size analyzer (Mastersizer 3000), and the volume-based cumulative particle size distribution of the particle size distribution determination is measured by laser diffraction method. D50 represents the particle size corresponding to the cumulative particle size distribution percentage reaching 50%.
[0082] In some embodiments, the primary sintering is carried out at a heating rate of 1°C / min to 20°C / min to a primary sintering temperature of 250°C to 1150°C and is kept warm for 3h to 12h. The primary sintering temperature may further be 500°C to 1000°C, and may be 250°C, 350°C, 400°C, 500°C, 600°C, 700°C, 800°C, 850°C, 900°C, 950°C, 1000°C, etc., and may be other values within the above range, which are not limited in this application. Appropriate heating rate, sintering temperature and holding time are helpful to pre-treat the first material to form a certain crystal structure, providing a basis for subsequent reaction with a metal reducing agent.
[0083] In some embodiments, the protective atmosphere may include at least one of argon, nitrogen, and helium to reduce the reaction of the first material with oxygen at high temperature to form oxides, thereby maintaining the purity and activity of the first material.
[0084] Step S2, mixing the first product with a metal reducing agent and performing secondary sintering to obtain a second product.
[0085] Specifically, the first product and the metal reducing agent are mixed evenly in a certain proportion, and then placed in a reaction device (such as a reactor), and a protective gas is introduced to replace the air, and secondary sintering is performed, and the second product is obtained after cooling. The addition of the metal reducing agent is intended to react chemically with the first product. For example, the first product formed by using silicon as the first material reacts with the metal reducing agent to form a silicon-metal compound or a silicon-metal alloy. The secondary sintering process also helps to ensure the uniformity and stability of the negative electrode material.
[0086] In some embodiments, the metal reducing agent may include at least one of magnesium powder, aluminum powder, and lithium powder. The above metal reducing agents all have good reducibility, which is beneficial to the reduction and alloying of the first product; at the same time, the introduction of the metal reducing agent also helps to improve the conductivity, ion diffusion performance and cycle stability of the negative electrode material.
[0087] In some embodiments, the mass ratio of the first product to the metal reducing agent is 1:(0.2-1.2), and can be 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1 or 1:1.2, etc., and can further be 1:(0.2-0.8). A suitable ratio can achieve a better reaction between the first product and the metal reducing agent.
[0088] In some embodiments, the secondary sintering is to increase the temperature to a primary sintering temperature of 250°C to 950°C at a heating rate of 1°C / min to 30°C / min and keep the temperature for 1h to 48h, and can be 250°C, 350°C, 400°C, 500°C, 600°C, 700°C, 800°C, 850°C, 900°C or 950°C, etc., wherein the secondary sintering temperature can further be 300°C to 600°C, and of course can be other values within the above range, which is not limited in this application. By appropriate heating rate, sintering temperature and holding time, it can be ensured that the reaction reaches a sufficient temperature and time, which can promote the reaction of the first product with the metal reducing agent, and improve the crystallinity and stability of the crystal structure of the second product.
[0089] Step S3, etching the second product to obtain a negative electrode material precursor.
[0090] Specifically, the second product obtained in step S2 is put into an etching solution in a certain proportion, and then purified under certain conditions, washed and dried to obtain a negative electrode material precursor. Acid etching can remove impurities such as metals and by-products on the surface of the second product to form a negative electrode precursor, improve the purity and activity of the negative electrode material precursor, and reduce the impact of impurities on the electrochemical properties of the material. The clean negative electrode material precursor provides a good foundation for the pore formation step and the subsequent deposition of the second material.
[0091] In some embodiments, the etching solution may include one of hydrochloric acid, nitric acid, sulfuric acid, and hydrofluoric acid, etc. These acidic solutions can effectively remove impurities such as metals and byproducts on the surface of the second product, and reduce the impact of impurities on the electrochemical properties of the subsequently prepared negative electrode material.
[0092] In some embodiments, the mass ratio of the second product to the etching solution can be 1:(5-20), and can be 1:5, 1:8, 1:10, 1:15 or 1:20, etc., and can also be other values within the above range, which are not limited in this application. By controlling the ratio of the second product to the etching solution, it is ensured that the surface of the second product is fully exposed during the etching process, and the etching effect is optimized.
[0093] In some embodiments, the molar concentration of the etching solution may be 1 mol / L to 10 mol / L. The molar concentration of the etching solution affects the concentration of active ions or molecules in the etching solution, directly affecting the etching rate and effect. Selecting an appropriate molar concentration can achieve an ideal etching effect in a shorter time while avoiding over-etching or incomplete etching.
[0094] In some embodiments, the etching reaction time may be 0.5 h to 10 h to ensure that the etching process is fully carried out so that impurities and unnecessary surface substances are completely removed.
[0095] In some embodiments, the temperature of the etching reaction is less than or equal to 35° C. Controlling a lower etching reaction temperature helps to avoid an excessively fast chemical reaction rate and maintain the controllability and safety of the etching process.
[0096] In some embodiments, the mass content of oxygen in the negative electrode material precursor is less than 5%. Controlling the oxygen content can reduce the negative impact of impurities on the electrochemical properties of the material and ensure the electrochemical activity and stability of the negative electrode material precursor.
[0097] In some embodiments, the mass content of water in the negative electrode material precursor may be less than 1.2%. Low water content helps to reduce the oxidation reaction of the negative electrode material precursor and maintain the purity and stability of the negative electrode material precursor.
[0098] In some embodiments, the median particle size of the negative electrode material precursor may be 0.1µm to 15µm, and may be 0.1µm, 0.2µm, 0.5µm, 1µm, 2µm, 5µm, 10µm or 15µm, etc., and may further be 1µm to 10µm, and of course may also be other values within the above range, which are not limited here. The median particle size affects the uniformity and surface area of the negative electrode material precursor, and the appropriate particle size range helps to optimize the electrochemical reaction rate and energy storage capacity of the negative electrode material.
[0099] In some embodiments, the silicon grain size of the negative electrode material precursor may be 0.2 nm to 15 nm, and may be 0.2 nm, 0.5 nm, 1 nm, 2 nm, 5 nm, 8 nm, 10 nm, 12 nm or 15 nm, and may further be 2 nm to 15 nm, and may also be other values within the above range, which are not limited here. Within the above range, the electrochemical reaction and the rapid charge transfer are facilitated, thereby improving the electrochemical performance of the negative electrode material.
[0100] In some embodiments, the porosity of the negative electrode material precursor may be 25% to 55%, and may be 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1 or 1:1.2, etc., and may further be 35 to 55%, and of course, may also be other values within the above range, which are not limited here. On the one hand, a moderate porosity helps to increase the specific surface area of the negative electrode material and the permeability of the electrolyte, promote the electrochemical reaction and the stability of the material; on the other hand, it provides a basis for the subsequent deposition of the second material and the formation of pores.
[0101] In some embodiments, the specific surface area of the negative electrode material precursor can be 250 m 2 / g~550m 2 / g, which can be 250m 2 / g、300m 2 / g, 350m 2 / g, 400m 2 / g, 450m 2 / g、500m 2 / g or 550m 2 / g, etc., and can be further increased to 200m 2 / g~500m 2 / g, and of course, it can also be other values within the above range, which is not limited here. Within the above range, the negative electrode material precursor has a higher specific surface area, which is conducive to the subsequent contact reaction with the second material.
[0102] In some embodiments, the pore volume of the negative electrode material precursor may be 0.28 cm 3 / g~0.56cm 3 / g, which can be 0.28 cm 3 / g, 0.3cm 3 / g, 0.4cm 3 / g, 0.5cm 3 / g or 0.56cm 3 / g, etc., and can be further 0.3cm 3 / g~0.5cm3 / g, and of course, it can also be other values within the above range, which are not limited here. The higher pore volume in the negative electrode material precursor provides space for the subsequent deposition of the second material and ensures sufficient space to form the necessary pores to optimize the performance and stability of the negative electrode material.
[0103] Step S4, depositing a second material inside particles of the negative electrode material precursor by pulsed chemical vapor deposition to obtain a negative electrode material.
[0104] Specifically, a negative electrode material precursor with a porous structure is placed in a reaction device (such as a reaction furnace), the air therein is replaced by a protective gas, and after being heated to a certain temperature, a gas-phase second material is introduced by pulse air intake. By controlling the amount of gas entering in a short time, the internal second material deposition rate and efficiency are changed, and then the second material is continuously introduced to continue to deposit the carbon source in the pores inside the particles of the negative electrode material precursor. After a certain period of insulation, the second material undergoes a thermal cracking reaction, so that the second material is deposited inside the negative electrode material precursor, and holes are reserved inside the negative electrode material precursor to obtain the negative electrode material.
[0105] In this step, the second material is deposited inside the negative electrode material precursor by pulse chemical vapor deposition and holes are reserved. By adopting the pulse gas intake method, the deposition rate of the second material inside the negative electrode material precursor can be accurately controlled, and the deposition rate is controlled to increase from the inside to the outside. The second material can be deposited inside the negative electrode material precursor while reserving a part of the holes, thereby adjusting the pore volume of the negative electrode material and controlling the particle space collapse ratio of the negative electrode material.
[0106] In some embodiments, the second material may include a carbon material, and the carbon material may include at least one of artificial graphite, natural graphite, amorphous carbon, activated carbon, mesophase carbon microbeads, carbon nanotubes, carbon nanofibers, and graphene. The second material is selected from the above materials, which can all play a role in depositing inside the negative electrode material precursor to form a conductive network.
[0107] In some embodiments, the second material may include a non-carbon material, and the non-carbon material may include at least one of a metal, a metal oxide, a silicide, a silicate, a phosphate, a titanate, an aluminum borate, and the like.
[0108] In some embodiments, the metal oxide may include at least one of aluminum oxide, zirconium oxide, germanium dioxide, and manganese dioxide.
[0109] In some embodiments, the silicide may include at least one of silicon carbide and silicon nitride.
[0110] In some embodiments, the silicate may include at least one of cordierite, mullite and zeolite. It is understood that the silicate of the present application is mainly a natural silicate mineral, wherein cordierite (magnesium aluminum silicate) has a chemical formula of Mg2Al4Si5O 18 , which may contain elements such as Na, K, Ca, Fe and Mn and H2O; mullite, whose chemical formula is 3Al2O3-2SiO2; zeolite (aluminosilicate), whose chemical formula is A m B p O 2p ·nH2O, where A represents cations, usually monovalent or divalent metal ions such as Ca, Na, K, Ba, Sr, etc., B represents the basic units that constitute the zeolite framework structure, namely Si and Al atoms, p is the valence of the cation, m is the number of cations A, and n is the number of water molecules.
[0111] In some embodiments, the phosphate may include at least one of aluminum phosphate, magnesium phosphate, calcium phosphate, titanium phosphate, chromium phosphate, cobalt phosphate, nickel phosphate, germanium phosphate, zirconium phosphate, niobium phosphate, molybdenum phosphate, tantalum phosphate, tungsten phosphate, and lanthanum phosphate.
[0112] In some embodiments, the titanate may include at least one of calcium titanate, iron titanate, lithium titanate, barium titanate, and the like.
[0113] In some embodiments, the heating rate of the vapor phase carbon deposition can be 1°C / min to 30°C / min. Controlling the heating rate can affect the transmission and decomposition rate of the second material in the reaction device. An appropriate heating rate can uniformly heat the negative electrode material precursor in the reaction chamber to a reaction temperature suitable for thermal cracking of the second material, while avoiding excessively fast heating that leads to non-uniform deposition or other adverse reactions.
[0114] In some embodiments, the reaction temperature of the vapor deposition may be 200°C to 1050°C, and may be 200°C, 300°C, 350°C, 400°C, 500°C, 600°C, 700°C, 800°C, 850°C, 900°C, 950°C, 1000°C or 1050°C, etc., and may be other values within the above range, which are not limited in this application, and may further be 500°C to 1000°C. The reaction temperature is a key parameter affecting the thermal cracking reaction rate and deposition quality of the second material. By reacting within an appropriate temperature range, the thermal cracking rate of the second material can be controlled, so that the second material is deposited inside the negative electrode material precursor and the desired pores are formed.
[0115] In some embodiments, the holding time of the vapor deposition may be 1 hour to 24 hours. Sufficient holding time is beneficial to ensure uniform deposition of the second material inside the negative electrode material precursor to form a stable structure and pore distribution.
[0116] In some embodiments, the gas-phase carbon source may include at least one of acetylene, methane, ethylene, propane, toluene, cyclohexane, ethanol, ethylene, propylene, pyrrole, acetonitrile, and the like.
[0117] In some embodiments, the flow rate of the gas-phase carbon source can be 0.1L / min~10L / min, and can be 0.1L / min, 0.5L / min, 1L / min, 2L / min, 3L / min, 4L / min, 5L / min, 6L / min, 7L / min, 8L / min, 9L / min or 10L / min, etc., and can also be other values within the above range, which are not limited in this application, and can further be 0.5L / min~5L / min. Controlling the flow rate of the gas-phase carbon source can adjust the rate and concentration of the carbon source entering the reaction device, thereby accurately controlling the carbon deposition rate of the carbon source in the negative electrode material precursor.
[0118] In some embodiments, the pulse frequency may be 10 Hz to 500 Hz, and the pulse duration may be 10 ms to 800 ms. The pulsed air intake may control the short-term high-concentration input of the second material, and the deposition process of the second material may be precisely controlled by adjusting the pulse frequency and duration.
[0119] In some embodiments, the pulse duration is 1h~8h. The pulse duration affects the deposition amount of the second material and the continuity of the reaction. An appropriate pulse duration can achieve sufficient deposition of the second material and form the required pores, thereby optimizing the electrochemical performance and cycle stability of the prepared negative electrode material.
[0120] Furthermore, the coating material can be deposited on the surface of the negative electrode material precursor by pulsed chemical vapor deposition to form a coating layer on the surface of the negative electrode material precursor, which is beneficial to reduce the amount of active substances dissolved in the negative electrode material during the cycle, thereby reducing the side reactions caused by the dissolved silicon particles in contact with the electrolyte; it is also beneficial to alleviate the volume expansion of the negative electrode material.
[0121] In some embodiments, the coating material may include a carbon material, and the carbon material may include at least one of graphene, soft carbon, and hard carbon. Reasonable design of the carbon material raw material of the negative electrode material can effectively inhibit the volume expansion of silicon particles and reduce the structural damage of the negative electrode material during the cycle; it can also enhance the mechanical strength and compressive resistance of the negative electrode material.
[0122] In some embodiments, the coating material may include a metal oxide layer, and the material of the metal oxide layer may include at least one of titanium oxide, aluminum oxide, lithium oxide, cobalt oxide, and vanadium oxide.
[0123] In some embodiments, the coating layer may include a nitride layer, and the material of the nitride layer may include at least one of titanium nitride, vanadium nitride, cobalt nitride, nickel nitride and carbon nitride.
[0124] The appropriate particle space collapse ratio of the negative electrode material and the uniform coating layer on the surface of the negative electrode material can improve the structural stability of the negative electrode material during the lithiation process, reduce the expansion rate of the negative electrode material, and be beneficial to the formation of a stable solid electrolyte film on the surface of the negative electrode material. It is also beneficial to improve the conductivity of the negative electrode material, thereby improving the electrochemical performance of the negative electrode material.
[0125] Compared with the prior art, the method for preparing the negative electrode material provided in the embodiment of the present application has the following beneficial effects:
[0126] 1. The pulsed chemical vapor deposition process can accurately control the deposition rate of the second material inside the negative electrode material, and control the deposition rate from the inside to the outside to increase in sequence, so that while depositing the second material inside the negative electrode material precursor, a part of the pores is reserved, and then the pore volume of the negative electrode material is accurately adjusted, and the particle space collapse ratio of the negative electrode material is controlled, so as to improve the structural stability of the negative electrode material and improve the cycle performance and rate performance of the negative electrode material.
[0127] 2. A uniform coating layer can also be formed on the surface of the negative electrode material through the pulsed chemical vapor deposition process. The uniform coating layer can further improve the structural stability of the negative electrode material during the lithiation process, reduce the expansion rate of the negative electrode material, and is conducive to forming a stable solid electrolyte film on the surface of the negative electrode material to improve the cycle performance of the negative electrode material, and is also conducive to improving the conductivity of the negative electrode material, thereby improving the electrochemical performance of the negative electrode material.
[0128] 3. This preparation method is simple, efficient, and highly controllable, which is conducive to the large-scale production of negative electrode materials and has excellent commercial prospects.
[0129] See also Figure 2 As shown, the embodiment of the present application also provides a battery, the battery 100 includes a positive electrode sheet 10, a negative electrode sheet 20, a separator 30 and an electrolyte 40, wherein the negative electrode sheet 20 includes a negative electrode active material, and the negative electrode active material is the negative electrode material as described above. The battery 100 prepared using the above-mentioned negative electrode material has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion.
[0130] The above-mentioned negative electrode material, preparation method thereof, and battery are further described below through specific examples.
[0131] Example 1
[0132] Step 1: Place silicon monoxide material in an atmosphere furnace, and heat to 950° C. at a heating rate of 3° C. / min under the protection of an argon atmosphere, keep warm for 5 hours, and then cool to obtain the first product.
[0133] Step 2: Mix the first product and metal aluminum powder in a mass ratio of 1:0.3, put them into a reactor, introduce protective gas to replace the air, heat to 650°C at a heating rate of 3°C / min, keep warm for 4 hours, and then cool to obtain the second product.
[0134] Step 3: put the second product into the etching solution for purification, the mass ratio of the second product to the etching solution is 1:5, the concentration of the etching solution is 6 mol / L, the etching reaction time is 1.5 h, the etching reaction temperature is controlled at 25°C, and the negative electrode material precursor is obtained after washing and drying.
[0135] Step 4: Place 500 g of the negative electrode material precursor into a rotary atmosphere furnace, replace the air therein with an inert gas, and heat to 750 ° C at a heating rate of 3 ° C / min under the protection of argon atmosphere. Set the acetylene gas flow rate to 2.5 L / min, and pass the carbon source into the pulse generator. Set the pulse frequency to 50 Hz, the pulse duration to 200 ms, and the pulse duration to 3 hours. After turning off the pulser, continue to pass acetylene gas at a flow rate of 2.5 L / min for 2 hours, and cool to obtain the negative electrode material.
[0136] Example 2
[0137] Step 1: Place the silicon monoxide material in an atmosphere furnace, and heat it to 970° C. at a heating rate of 3° C. / min under the protection of an argon atmosphere, keep it warm for 6 hours, and then cool it to obtain the first product.
[0138] Step 2: Mix the first product and metal aluminum powder in a mass ratio of 1:0.3, put them into a reactor, introduce protective gas to replace the air, heat to 650°C at a heating rate of 3°C / min, keep warm for 4 hours, and then cool to obtain the second product.
[0139] Step 3: put the second product into the etching solution for purification, the mass ratio of the second product to the etching solution is 1:10, the concentration of the etching solution is 3 mol / L, the etching reaction time is 2.5 h, the etching reaction temperature is controlled at 25°C, and the negative electrode material precursor is obtained after washing and drying.
[0140] Step 4: Place 500 g of the negative electrode material precursor into a rotary atmosphere furnace, replace the air therein with an inert gas, and heat to 700 ° C at a heating rate of 3 ° C / min under the protection of argon atmosphere. Set the acetylene gas flow rate to 0.5 L / min, and pass the carbon source into the pulse generator. Set the pulse frequency to 500 Hz, the pulse duration to 10 ms, and the pulse duration to 8 hours. After turning off the pulser, continue to pass acetylene gas at a flow rate of 2.5 L / min for 1 hour, and cool to obtain the negative electrode material.
[0141] Example 3
[0142] Step 1: Place the silicon monoxide material in an atmosphere furnace, and heat it to 970° C. at a heating rate of 3° C. / min under the protection of an argon atmosphere, keep it warm for 6 hours, and then cool it to obtain the first product.
[0143] Step 2: Mix the first product and metal aluminum powder in a mass ratio of 1:0.3, put them into a reactor, introduce protective gas to replace the air, heat to 650°C at a heating rate of 3°C / min, keep warm for 4 hours, and then cool to obtain the second product.
[0144] Step 3: put the second product into the etching solution for purification, the mass ratio of the second product to the etching solution is 1:10, the concentration of the etching solution is 3 mol / L, the etching reaction time is 2.5 h, the etching reaction temperature is controlled at 25°C, and the negative electrode material precursor is obtained after washing and drying.
[0145] Step 4: Place 500 g of the negative electrode material precursor into a rotary atmosphere furnace, replace the air therein with an inert gas, and heat to 900 ° C at a heating rate of 3 ° C / min under the protection of argon atmosphere. Set the acetylene gas flow rate to 9.5 L / min, and pass the carbon source into the pulse generator. Set the pulse frequency to 10 Hz, the pulse duration to 800 ms, and the pulse duration to 4 hours. After turning off the pulser, continue to pass acetylene gas at a flow rate of 1.5 L / min for 2 hours, and cool to obtain the negative electrode material.
[0146] Example 4
[0147] Step 1: Place silicon monoxide material in an atmosphere furnace, and heat to 950° C. at a heating rate of 3° C. / min under the protection of an argon atmosphere, keep warm for 5 hours, and then cool to obtain the first product.
[0148] Step 2: Mix the first product and metal magnesium powder in a mass ratio of 1:0.2, put them into a reactor, introduce protective gas to replace the air, heat to 620°C at a heating rate of 3°C / min, keep warm for 5 hours, and then cool to obtain the second product.
[0149] Step 3: put the second product into the etching solution for purification, the mass ratio of the second product to the etching solution is 1:10, the concentration of the etching solution is 5 mol / L, the etching reaction time is 1.5 h, the etching reaction temperature is controlled at 25°C, and the negative electrode material precursor is obtained after washing and drying.
[0150] Step 4: Place 500 g of the negative electrode material precursor into a rotary atmosphere furnace, replace the air therein with an inert gas, and heat to 950 ° C at a heating rate of 3 ° C / min under the protection of argon atmosphere. Set the acetylene gas flow rate to 10 L / min, and pass the carbon source into the pulse generator. Set the pulse frequency to 10 Hz, the pulse duration to 800 ms, and the pulse duration to 8 hours. After turning off the pulser, continue to pass acetylene gas at a flow rate of 0.1 L / min for 3 hours, and cool to obtain the negative electrode material.
[0151] Example 5
[0152] The specific process of the preparation process refers to Example 1, except that the pulse frequency in step 4 is 20 Hz. The preparation method of the remaining negative electrode materials is basically the same as that in Example 1, and will not be described in detail here.
[0153] Example 6
[0154] The specific process of the preparation process refers to Example 1, except that the pulse frequency in step 4 is 100 Hz. The preparation method of the remaining negative electrode materials is basically the same as that in Example 1, and will not be described in detail here.
[0155] Example 7
[0156] The specific process of the preparation process refers to Example 1, except that the pulse duration in step 4 is 1 hour. The preparation method of the remaining negative electrode materials is basically the same as that in Example 1, and will not be described in detail here.
[0157] Example 8
[0158] The specific process of the preparation process refers to Example 1, except that the pulse duration in step 4 is 6 hours. The preparation method of the remaining negative electrode materials is basically the same as that in Example 1, and will not be described in detail here.
[0159] Comparative Example 1
[0160] The specific process of the preparation process refers to Example 1, except that the carbon deposition in step 4 is a traditional chemical vapor deposition (CVD) technology, specifically, 500g of the negative electrode material precursor is placed in a rotary atmosphere furnace, the air therein is replaced with an inert gas, and under the protection of an argon atmosphere, the temperature is heated to 750°C at a heating rate of 3°C / min, and the acetylene gas flow rate is set to 2.5L / min, and acetylene gas is continuously introduced for 5h, and the negative electrode material is obtained by cooling. The preparation method of the remaining negative electrode materials is basically the same as in Example 1, and will not be described in detail here.
[0161] The negative electrode materials obtained in Examples 1-8 and Comparative Example 1 were subjected to the following tests.
[0162] 1. The negative electrode materials obtained in Examples 1-8 and Comparative Example 1 were tested for specific surface area, pore volume, particle space collapse ratio P, particle size, tap density, oxygen content, carbon content, scanning electron microscopy, X-ray diffraction, average size of primary particles and average size of silicon grains. The results are shown in Table 1. For example, the scanning electron microscopy results of the negative electrode material in Example 1 are as follows: Figure 3 As shown, the X-ray diffraction pattern of the negative electrode material in Example 1 is as follows Figure 4 shown.
[0163] (1) Test methods for specific surface area and specific pore volume of negative electrode materials:
[0164] Using the ASAP2460 surface area and pore size analyzer from Micromeritics, USA, at liquid nitrogen temperature, the equilibrium adsorption amount of nitrogen on the surface of an object is related to its specific surface area and other characteristics. Combined with the law of change of adsorption amount with relative pressure during the adsorption process, multiple models can be fitted to calculate the specific surface area and specific pore volume.
[0165] (2) The spatial collapse ratio P of the negative electrode material particles is tested by the following test method:
[0166] Take 1kg of negative electrode material, measure the pore volume as M, then put the composite material into an aluminum-plastic film bag, evacuate it, control the vacuum degree below 10kpa, and then seal the aluminum-plastic film bag. Put the aluminum-plastic film bag into an isostatic pressing device, set the pressure to 80Mpa, and maintain the pressure for 1h. The pore volume of the composite material is N, and the particle space collapse ratio P = (MN) / M is calculated.
[0167] (3) Particle size of negative electrode material:
[0168] The median particle size test method refers to GB / T 19077-2016. It can be conveniently measured using a laser particle size analyzer, such as the Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0169] (4) Testing method for tap density:
[0170] Using a vibrator, weigh a certain amount of sample and vibrate 3000 times at 300 times / min to test the tap density.
[0171] (5) Test methods for oxygen content and carbon content:
[0172] The oxygen content was measured by Fourier transform infrared spectrometer, and the overall carbon content was tested by thermogravimetric analysis.
[0173] (6) SEM test:
[0174] SEM characterization was performed on a transmission electron microscope with an operating voltage of 200 kV to observe the structure of the negative electrode material and to scale the thickness of the coating layer.
[0175] (7) Test method for average size of primary particles:
[0176] The material is sectioned using a FIB-SEM device, and the sizes of 20 primary particles are measured in the SEM. The result is then averaged and the average size is taken as the average size of the primary particles.
[0177] (8) Test method for average silicon grain size:
[0178] The XRD spectrum of the sample was measured by X-ray diffractometer, the half-height width of the diffraction peak of the sample and the corresponding Bragg angle were obtained by jade software, and the average grain size of nano-silicon was calculated by Scherrer formula D=Kγ / B cosθ.
[0179]
[0180] 2. The electrochemical performance of the negative electrode materials obtained in Examples 1-8 and Comparative Example 1 was tested. The results are shown in Table 2.
[0181] The negative electrode material was mixed with sodium carboxymethyl cellulose, styrene-butadiene rubber, conductive graphite (KS-6) and carbon black (SP) in a ratio of 92:2:2:2:2 to prepare a slurry, uniformly coated on a copper foil and dried to make a negative electrode sheet, which was assembled into a button cell in an argon atmosphere glove box. The separator used was a polypropylene microporous membrane, the electrolyte used was 1 mol / L lithium hexafluorophosphate (the solvent was a mixture of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate), and the counter electrode used was a metal lithium sheet.
[0182] The above 9 groups of batteries were tested for discharge specific capacity on a Blue Power CT2001A battery testing system. The ratio of the discharge amount in one hour to the battery capacity is the discharge specific capacity.
[0183] The above 9 groups of batteries were subjected to the first coulombic efficiency test on the Blue Power CT2001A battery testing system, with the charge and discharge current of 0.05C, and the first coulombic efficiency was measured.
[0184] The above 9 groups of batteries were tested on the Blue Power CT2001A battery test system for 50 cycles, with a charge and discharge current of 0.25C. After 50 cycles, the battery capacity and capacity retention rate after the cycle were calculated, where the capacity retention rate after 50 cycles at 0.25C = the discharge capacity of the 50th cycle / the discharge capacity of the first week*100%. For example, the cycle performance curve of the battery prepared using the negative electrode material in Example 1 is as follows: Figure 5 shown.
[0185]
[0186] The above results show that:
[0187] Figure 3 This is a scanning electron microscope image of the negative electrode material in Example 1. Figure 3 It can be seen from the scanning electron microscope image that the surface of the negative electrode material is relatively smooth and the particles of the negative electrode material are not broken. Figure 4 is the XRD diagram of the negative electrode material in Example 1, from Figure 4 It can be seen from the XRD spectrum that the three strong peaks at 28.4°, 47.3° and 56.1° correspond to the three strong peaks of silicon (JCPDS No. 27-1402), and there is basically no impurity phase. According to the Scherrer formula, the silicon grain size can be calculated to be 3.5nm. After testing, the pore volume of the negative electrode material obtained in Example 1 is 0.09cm 3 / g, the particle space collapse ratio P is 0.25, the average size of the silicon grains in the negative electrode material is 3.5nm, the median particle size of the negative electrode material is 5μm, and the specific surface area is 5m 2 / g, the compacted density of the powder is 1.2g / cm 3 , oxygen content is 5%, carbon mass percentage content is 33%, and the average particle size of the primary particles of the silicon material in the negative electrode material is 10nm. The results show that the negative electrode material obtained in Example 1 has suitable pore volume and particle space collapse ratio P, and also has suitable specific surface area, high compaction density and other excellent performance parameters.
[0188] Figure 5 The cycle performance curve of the button cell prepared by using the negative electrode material in Example 1 is shown in FIG. Figure 5It can be seen that the button cell prepared by using the negative electrode material in Example 1 has excellent cycle performance, and the capacity retention rate can still reach 83.3% after 50 cycles at a current of 0.25C. This shows that the negative electrode material in this example has a suitable pore volume and particle space collapse ratio P, which not only improves the structural stability of the negative electrode material but also improves the cycle performance of the negative electrode material, thereby improving the electrochemical performance of the battery.
[0189] The negative electrode materials obtained in Examples 2-8 also have suitable pore volume and particle space collapse ratio P, as well as excellent properties such as suitable specific surface area and higher compaction density. The batteries made using the negative electrode materials obtained in Examples 2-8 also have characteristics such as higher specific capacity and first efficiency, significantly improved volume retention rate and lower expansion rate.
[0190] In Comparative Example 1, the conventional chemical vapor deposition technology is used. Since the carbon deposition rate of the carbon source inside the material cannot be accurately controlled to adjust the pore volume of the composite negative electrode material and control the particle space collapse ratio of the composite negative electrode material, the pore volume of the negative electrode material in Comparative Example 1 (0.21 cm 3 / g) is too large, which can easily cause deformation of the outer surface of the negative electrode material, thereby resulting in capacity decay and reduced cycle stability of the prepared battery; and the particle space collapse ratio (0.95) is too high, the rigidity of the negative electrode material is weak, and there are many internal pores. Although it can effectively alleviate the volume expansion of silicon, the volume shrinkage of the negative electrode material is large, which will cause the electrolyte to be absorbed into the material to cause side reactions, resulting in serious capacity decay.
[0191] It can be seen that compared with Comparative Example 1, the negative electrode materials obtained in Examples 1-8 have suitable pore volume and particle space collapse ratio P, and various structural data and electrochemical test results are excellent, indicating that the negative electrode materials in the examples of the present application have good structural stability, can effectively reduce the expansion rate, and exhibit excellent electrochemical performance.
[0192] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. A negative electrode material, characterized in that: The invention comprises an active material, wherein the active material comprises a first matrix and a second matrix, wherein the first matrix is a silicon-based material, the second matrix is a carbon material, at least part of the particles of the second matrix are located inside the particles of the first matrix and form pores together, the pore volume of the negative electrode material is M, the pore volume of the negative electrode material measured after being maintained at a pressure of 80 MPa for 1 hour is N, and the particle space collapse ratio of the negative electrode material is P, where P=(MN) / M, wherein 0.002 cm 3 / g≤M≤0.12cm 3 / g, 0.05≤P≤0.
85.
2. The negative electrode material according to claim 1, characterized in that The first substrate comprises a silicon-based material, and the silicon-based material satisfies at least one of the following conditions: (1) The silicon-based material includes amorphous silicon, crystalline silicon, or a composite of crystalline silicon and amorphous silicon; (2) The silicon-based material includes at least one of silicon oxide and silicon alloy.
3. The negative electrode material according to claim 1, characterized in that The carbon material includes at least one of artificial graphite, natural graphite, amorphous carbon, activated carbon, mesophase carbon microbeads, carbon nanotubes, carbon nanofibers and graphene.
4. The negative electrode material according to claim 3, characterized in that The negative electrode material further includes a coating layer, which is disposed on at least a portion of the surface of the active material, and the coating layer satisfies at least one of the following conditions: (1) The coating layer includes a carbon material, and the carbon material includes at least one of graphene, soft carbon and hard carbon; (2) The coating layer includes a metal oxide layer, and the material of the metal oxide layer includes at least one of titanium oxide, aluminum oxide, lithium oxide, cobalt oxide and vanadium oxide; (3) The coating layer includes a nitride layer, and the material of the nitride layer includes at least one of titanium nitride, vanadium nitride, cobalt nitride, nickel nitride and carbon nitride; (4) The thickness of the coating layer is 0.1 nm to 100 nm.
5. The negative electrode material according to claim 2, characterized in that The silicon-based material satisfies at least one of the following conditions: (1) The average particle size of the primary particles of the silicon-based material is 1 nm to 100 nm; (2) The average grain size of the silicon-based material is 0.5 nm to 15 nm.
6. The negative electrode material according to claim 1, characterized in that The negative electrode material satisfies at least one of the following conditions: (1) The median particle size of the negative electrode material is 0.2µm~15µm; (2) The specific surface area of the negative electrode material is 0.8 m 2 / g~15m 2 / g; (3) The average diameter of the pores is 0.5 nm to 20 nm; (4) The compacted density of the negative electrode material powder is 0.8 g / cm 3 ~1.5g / cm 3 .
7. The negative electrode material according to claim 1, characterized in that Calculated by mass percentage, the negative electrode material satisfies at least one of the following conditions: (1) The second matrix is a carbon material, and the content of carbon in the negative electrode material is 5% to 70% based on the mass of the negative electrode material; (2) Based on the mass of the negative electrode material, the content of oxygen in the negative electrode material is less than or equal to 10%.
8. A battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet comprises the negative electrode material according to any one of claims 1 to 7.
Citation Information
Patent Citations
Negative electrode active material composite and preparation method thereof, negative electrode, and rechargeable lithium battery
CN116072860A
Cited By
Negative electrode material and battery
EP4822776A1